Estudio de prefactibilidad para la implementación de una planta procesadora de snacks de oca frita - Becerra Arriola, Katia Elisabet (2016)
In this work is showed a study of pre-feasibility for the implementation of a processing plant to produce fried yam snacks where the technical, economic and market viability is assessed.